PJMHS 2022
DOI: 10.53350/pjmhs22167906
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury During Pregnancy and Puerperium

Abstract: Background and Aim: Acute kidney injury (AKI) is a serious complication in perilous patients substantially related to long-term chronic kidney disease (CKD) with increased morbidity, hospital duration, and mortality. AKI during pregnancy is a life-threatening disease related to maternal and fetal loss contributing to 30% to 60% of mortality. Though a rare cases of AKI during pregnancy has been reported in previous studies. But the present study aimed to assess the acute kidney injury during pregnancy and puerp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Sepsis was the main cause of AKI in a study conducted by Mahesh et al [13], in contrast to a study conducted by Taj et al, which identified postpartum hemorrhage (eight cases, 18.2%) as the main cause [14], causing hypotension for the development of AKI in pregnancy. Preeclampsia/eclampsia (14 cases, 26.6%) is another common cause of AKI in our study, which is consistent with the study by Prakash et al, which reported preeclampsia and eclampsia to be the most common causes of pregnancy-related acute renal injury, contributing to 35.29% of cases [15].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Sepsis was the main cause of AKI in a study conducted by Mahesh et al [13], in contrast to a study conducted by Taj et al, which identified postpartum hemorrhage (eight cases, 18.2%) as the main cause [14], causing hypotension for the development of AKI in pregnancy. Preeclampsia/eclampsia (14 cases, 26.6%) is another common cause of AKI in our study, which is consistent with the study by Prakash et al, which reported preeclampsia and eclampsia to be the most common causes of pregnancy-related acute renal injury, contributing to 35.29% of cases [15].…”
Section: Discussionmentioning
confidence: 70%
“…edema(14, 22.58%), vomiting (4, 6.65%), altered sensorium (4, 6.45%), abdominal pain (3, 4.83%), and burning micturition (2, 3.22%).…”
mentioning
confidence: 99%
“…Several studies have linked pre-eclampsia and HELLP syndrome to acute renal damage. Acute kidney damage affects 3-10% of pregnant women with particular illnesses worldwide [6]. However, Bihar's disease prevalence is unknown.…”
Section: Occurrence and Risk Issuesmentioning
confidence: 99%
“…Pregnancy problems are more likely with advanced maternal age, first pregnancy, preeclampsia or HELLP syndrome, twins or more, hypertension, diabetes, and lack of prenatal care. Multiple pregnancies, hypertension, and diabetes increase the risk [7,8]. Identifying high-risk individuals and taking preventative steps requires understanding these risk factors.…”
Section: Occurrence and Risk Issuesmentioning
confidence: 99%